Granulomatous Conduit for Intrathecal Infusion of Morphine and Bupivacaine. Issue 2 (1st February 2011) - Webb, David M.; Schneider, John R.; Lober, Robert M.; Vender, John R.
Abstract : Objective: Intrathecal drug delivery systems (IT-DDSs) have gained more widespread use in patients with non-cancer-related pain, notably failed back surgery syndrome and spinal arachnoiditis. Secondary to the longer life spans of these patients, more complications have been discovered with IT-DDSs. With an estimated incidence of 1% to 3%, an uncommon but serious complication is that of granuloma formation. Case Report: We describe a case of a 38-year-old woman with a malfunctioning IT-DDS containing morphine and bupivacaine. The device had stopped providing relief for several months because of presumed leakage from the connection site between the pump and the proximal catheter. The IT-DDS spontaneously resumed functioning. The IT-DDS was explanted for low battery life, upon which we discovered that the leakage site had been encapsulated by drug concretion and granuloma formation, thus providing a sealed conduit that reestablished drug flow between the pump and the catheter. Conclusions: This case report reinforces the view that the infusate is the causal agent of this lesion.